The effect of conventional bank credit, Islamic bank financing, and Zakat distribution on GDP - CANIAGO, Muhammad Ali Imran; AZHAR, Jeihan Ali; WIBOWO, Muhammad Ghafur; SETYONO, Joko (Journal of process management and new technologies, 2024)
The growth of gross domestic product (GDP) is subject to a number of different influences. The objective of this study is to analyse the impact of conventional bank credit, Islamic bank financing and zakat distribution on gross domestic product. The study employs a sample comprising data from 33 provinces in Indonesia, spanning the period from 2018 to 2022. The data analysis technique employed is dynamic panel data regression utilising the Generalised Method of Moments (GMM) method. The findings indicated that partial conventional bank credit and zakat distribution exerted a notable positive influence on GDP. In contrast, the impact of Islamic bank financing on GDP is not statistically significant. This is due to the fact that the market share of Islamic banking in Indonesia remains relatively low, and access to financing in this sector is also still quite complex. Concurrently, conventional bank credit, Islamic bank financing, and zakat distribution exert a significant influence on GDP. The findings of this study suggest that the financing provided by Islamic banks has not yet been fully capable of boosting GDP, given that the share of Islamic bank financing in Indonesia remains relatively modest in comparison to conventional banks. Consequently, the results of this study can be utilized to inform the development of programs and policies for relevant stakeholders.